Regulatory microRNAs and phasiRNAs of paclitaxel biosynthesis in Taxus chinensis - Sun, Ming-Sheng; Jia, Yan; Chen, Xin-Yi; Chen, Ji-Shi; Guo, Ying; Fu, Fang-Fang; Xue, Liang-Jiao (Frontiers in Plant Science, 2024)
Paclitaxel (trade name Taxol) is a rare diterpenoid with anticancer activity isolated from Taxus. At present, paclitaxel is mainly produced by the semi-synthetic method using extract of Taxus tissues as raw materials. The studies of regulatory mechanisms in paclitaxel biosynthesis would promote the production of paclitaxel through tissue/cell culture approaches. Here, we systematically identified 990 transcription factors (TFs), 460 microRNAs (miRNAs), and 160 phased small interfering RNAs (phasiRNAs) in Taxus chinensis to explore their interactions and potential roles in regulation of paclitaxel synthesis. The expression levels of enzyme genes in cone and root were higher than those in leaf and bark. Nearly all enzyme genes in the paclitaxel synthesis pathway were significantly upregulated after jasmonate treatment, except for GGPPS and CoA Ligase. The expression level of enzyme genes located in the latter steps of the synthesis pathway was significantly higher in female barks than in male. Regulatory TFs were inferred through co-expression network analysis, resulting in the identification of TFs from diverse families including MYB and AP2. Genes with ADP binding and copper ion binding functions were overrepresented in targets of miRNA genes. The miRNA targets were mainly enriched with genes in plant hormone signal transduction, mRNA surveillance pathway, cell cycle and DNA replication. Genes in oxidoreductase activity, protein-disulfide reductase activity were enriched in targets of phasiRNAs. Regulatory networks were further constructed including components of enzyme genes, TFs, miRNAs, and phasiRNAs. The hierarchical regulation of paclitaxel production by miRNAs and phasiRNAs indicates a robust regulation at posttranscriptional level. Our study on transcriptional and posttranscriptional regulation of paclitaxel synthesis provides clues for enhancing paclitaxel production using synthetic biology technology.